Occupational Accident Prevention Training through Experiencing Stories of Success in Time Travel Prevention Games - Wache, Hans-Holger; Franke, Ronny; Arnold, Oksana; Jantke, Klaus P. (International Journal of Advanced Corporate Learning (iJAC), 2025)
Fiction is an ancient virtual reality technology that specializes in simulating human problems. The stories told are the media and, according to Marshall McLuhan, the medium is the message. The technology is interwoven with up to date digital media design and information technologies including artificial intelligence (AI). According to Keith Oatley, stories are the flight simulators of human social life. From the many fields of human life, emphasis is put on the training of occupational accident prevention. The potential of storytelling is deployed for the prevention of accidents to preserve human lives, to avoid human injuries, the damage of installations and financial losses. Aiming at effectiveness and sustainability, the task under consideration is the interdisciplinary design of spaces of stories with a high educational potential. The authors abandon the educational paradigm of telling stories of disaster. Interactive digital storytelling is tailored to allow for unprecedented learner engagement in stories of success. Prevention training is designed to appear playfully based on the original concept of time travel prevention games. Trainees who failed to complete their task—thereby possibly ruining a (fortunately only virtual) technical installation—are enabled to travel back in time to do better the next time. AI guides the trainees to a success of their own. In the condition of training with time travel prevention games, designing spaces of stories to be experienced playfully is an ambitious variant of gamification. The design of stories in story spaces is a particularly complex case of dynamic AI planning. Patterns that occur in story spaces wrap educational theory as well as ideas of game design. The plan generation concepts foster interdisciplinary co-operation of educators, domain experts, VR specialists, game designers, psychologists, and others in creating spaces of affective stories of success.